Process integration of CO2 capture by means of calcium looping technology - Fransson, Eric; Detert, Merle (My University, 2014)
Carbon capture and storage (CCS) can play a significant role in the attempt to mitigate climate change. Among the technologies today available for CO2 capture, calcium looping exploits the reaction that takes place at medium temperatures between lime (CaO) and CO2 to form limestone (CaCO3) which can be reversed at higher temperatures to release pure CO2. The process is based on well-known technology but its application for CO2 capture has been suggested only recently and is less established than other CO2 capture technologies such as chemical absorption using amines or ammonia as solvents. A reason for this is that fuel is needed to provide high temperature heat. Thus carbon capture by calcium looping can represent a competitive solution where fuel is available in large quantities like in coal power plants. In addition, since a certain quantity of spent sorbent is obtained from the calcium looping, an interesting application arises when this spent lime can be further used for other purposes. This is the case of the cement industry where lime from the calcium looping can reduce the demand of fresh limestone and the energy consumption for its calcination into lime. The aim of this thesis is to investigate the process integration opportunities of carbon capture by the calcium looping technology mainly from a thermodynamic point of view and for the two most relevant application cases: coal power plant and cement industry. Pinch analysis is used as a tool for estimating the consequences of calcium looping application on the process heat and power balances under ideal heat recovery conditions. For this purpose, process modelling and simulation is conducted to obtain temperature and heat load information of the different system parts. The work is organised in two parts discussing the integration aspects of calcium looping with a state of the art coal power plant and a combined power and cement production plant respectively. Three configurations are considered for integration of calcium looping with the coal power plant: two cases assuming a separate steam cycle to recover the excess heat from the calcium looping process (each case with different complexity of the steam cycle) and one case where heat from the coal plant and calcium looping process are recovered and used in the same steam cycle. To assess the integration effect of carbon capture the penalty on the power plant thermal efficiency is used as an indicator. For comparison oxy-fuel coal combustion technology and subsequent CO2 separation by water condensation is also investigated. The case where calcium looping and the coal power plant are integrated with the same steam cycle achieves the best result in terms of electrical efficiency, with a penalty of 5.3%-points compared to a reference coal plant without calcium looping (from 42.8% to 37.5%). The analysis of integration between coal power plant, cement production plant and calcium looping is conducted considering two cases: the first where the cement plant output is kept equal to the reference plant, and the second where the cement output is adjusted to completely replace the limestone input with the spent sorbent from the calcium looping. The integration effects are assessed considering different indicators, such as the thermal efficiency penalty with respect the reference power plant, the specific fuel consumption for cement production, the reduction in specific GHG-emissions from the combined cement and power production. In the case of limestone free cement production the further integration of cement production with coal power plant and calcium looping contributes to a minor reduction in thermal efficiency (from 37.5% to 37.3%).
Keywords: Energi; Kemiteknik; Hållbar utveckling; Kemiska processer; Energy; Chemical Engineering; Sustainable Development; Chemical Process Engineering